2002
DOI: 10.1128/jcm.40.4.1363-1367.2002
|View full text |Cite
|
Sign up to set email alerts
|

New Yeast Species, Malassezia dermatis , Isolated from Patients with Atopic Dermatitis

Abstract: Malassezia species are considered to be one of the exacerbating factors in atopic dermatitis (AD). During examination of the cutaneous colonization of Malassezia species in AD patients, we found a new species on the surface of the patients' skin. Analysis of ribosomal DNA sequences suggested that the isolates belonged to the genus Malassezia. They did not grow in Sabouraud dextrose agar but utilized specific concentrations of Tween 20, 40, 60, and 80 as a lipid source. Thus, we concluded that our isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
136
0
13

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(151 citation statements)
references
References 30 publications
2
136
0
13
Order By: Relevance
“…Nucleotide sequence analysis of the 26S rDNA (D1/D2 regions) of these isolates showed fewer than five substitutions over 577 bp among them; the isolates differed by >23 substitutions over 577 bp from the eight Malassezia species that have been reported previously (Fell et al, 2000;Sugita et al, 2002). The difference between these isolates and the eight Malassezia species exceeded that generally observed between species (Scorzetti et al, 2002).…”
mentioning
confidence: 74%
See 2 more Smart Citations
“…Nucleotide sequence analysis of the 26S rDNA (D1/D2 regions) of these isolates showed fewer than five substitutions over 577 bp among them; the isolates differed by >23 substitutions over 577 bp from the eight Malassezia species that have been reported previously (Fell et al, 2000;Sugita et al, 2002). The difference between these isolates and the eight Malassezia species exceeded that generally observed between species (Scorzetti et al, 2002).…”
mentioning
confidence: 74%
“…Recently, an eighth species of Malassezia, newly isolated from the skin of a human with atopic dermatitis, was described as Malassezia dermatis by using molecular analysis (Sugita et al, 2002). As a result of molecular analysis, we suggested that an isolate from a cat might belong to a novel species of the genus Malassezia (Hirai et al, 2002).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Recently, other new Malassezia species have been reported, namely M. japonica (21) and M. dermatis (22), and these may be similar to some of the unclassified species referred above.…”
Section: Discussionmentioning
confidence: 80%
“…New questions have been raised about the significance and relationships of the Malassezia species in clinical infections (1,4), this is due to factors such as the recent description of new species (2,21,22), the isolation of Malassezia as part of the microbial community of human skin rich in sebaceous glands (1,2,6,16), and the variability in colonization according to different age groups and sebaceous glands activity (15,19,23).…”
Section: Discussionmentioning
confidence: 99%